Blood gas analysis in pigs submitted to different concentrations of nitrous oxide or oxygen, under different ventilatory modalities - Bum, E. G. F. [UNESP]; Nunes, N. [UNESP]; Lopes, P. C. F.; Silva, P. E. S. [UNESP]; Ido, C. K. [UNESP]; Silva, H. R. A. [UNESP]; Horr, M. [UNESP]; Carneiro, R. L. [UNESP]; Bompadre, T. F. (Arquivo Brasileiro Medicina Veterinaria Zootecnia, 2019)
The effects of different concentrations of oxygen and nitrous oxide on blood gas parameters in pigs maintained under spontaneous or pressure-controlled ventilation, with or without positive end-expiratory pressure (PEEP), were compared. Forty-eight pigs were randomly divided into six groups, submitted to different concentrations of compressed air or N2O, associated with different fractions of inspired oxygen (FiO(2)). The group subject to 30% of compressed air (GA30) showed the closest proximity to the physiological range of partial pressure (PaO2) expected for the species. For oxygen saturation (SaO(2)), the values obtained were below the lower physiological limit in the group administered 30% N2O (GN30). Use of PEEP positively interfered in PaCO2 independent of FiO(2), however, its effectiveness can be compromised when complemented by N2O-based anesthesia. For SaO(2), only GN30 showed values lower than adequate for maintaining tissue oxygenation. The pH, base deficit and bicarbonate in arterial blood were influenced by FiO(2) and N2O. In conclusion, the use of compressed air maintains blood gas parameters at their most stable, especially GA30 and PEEP, which seemed to positively influence the experimental groups, with some interference from FiO(2) and N2O.
Keywords: alkylphenol; atelectasis; pigs; respiration